2016
DOI: 10.1024/0301-1526/a000561
|View full text |Cite
|
Sign up to set email alerts
|

Surgical and endovascular hybrid approach in peripheral arterial disease of the lower limbs

Abstract: We treated all of the patients in an operating theatre equipped with a dedicated portable C arm with a specifi c capacity for road mapping and image analysis (BV Pulsera, Philips, DA Best, and the Netherlands) associated with a radiolucent imaging Summary: Background: Multilevel peripheral arterial disease is frequently observed in patients with intermittent claudication or critical limb ischemia. This report evaluates the effi cacy of one-stage hybrid revascularization in patients with multilevel arterial per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 14 publications
0
7
0
1
Order By: Relevance
“…The outcomes of this large multicenter database analysis are consistent with reported single-center series of morbidity (3%-7%) and mortality (1.1%-6.4%) of hybrid procedures for lower extremity revascularization. 8,[17][18][19][20][21] Most case series are relatively small and just report on periprocedural complications and long-term outcomes regarding patency and limb salvage. 17,[22][23][24] Some compare hybrid procedures on the basis of indications such as claudication, CLI, and acute limb ischemia or the direction of the endovascular intervention (inflow vs outflow).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The outcomes of this large multicenter database analysis are consistent with reported single-center series of morbidity (3%-7%) and mortality (1.1%-6.4%) of hybrid procedures for lower extremity revascularization. 8,[17][18][19][20][21] Most case series are relatively small and just report on periprocedural complications and long-term outcomes regarding patency and limb salvage. 17,[22][23][24] Some compare hybrid procedures on the basis of indications such as claudication, CLI, and acute limb ischemia or the direction of the endovascular intervention (inflow vs outflow).…”
Section: Discussionmentioning
confidence: 99%
“…8,[17][18][19][20][21] Most case series are relatively small and just report on periprocedural complications and long-term outcomes regarding patency and limb salvage. 17,[22][23][24] Some compare hybrid procedures on the basis of indications such as claudication, CLI, and acute limb ischemia or the direction of the endovascular intervention (inflow vs outflow). 13,18,19 Dosluoglu et al 20 compared hybrid revascularization with open and endovascular therapy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Limb salvage rates at 12 and 36 months in patients with CLI were similar in the endovascular, sHYBRID, and open groups (86 % and 80 %, 94 % and 80 %, and 80 % and 74 %, respectively); however, these rates were improved in the cHYBRID group (100 %; P = 0.014). Granjean et al [25] reported European results with a technical success rate of 100 %. The primary, primary-assisted and secondary patency rates at one year were 39 %, 66 %, and 81 %, respectively.…”
Section: Revascularization Proceduresmentioning
confidence: 96%